CHEMICAL COMPOSITION OF UNRIPE AND RIPE FRUITS OF CLUSTER FIG (FICUS GLOMERATA - DIPALI Y JADHAV,; AKSHAYA K SAHOO, (International Journal of Pharma and Bio Sciences, 2016)
Cluster fig (Ficus glomerata) plant is well known for its medicinal importance in Ayurveda. Though the plant parts of cluster fig such as leaves, roots, bark and latex were used as medicine and proved for its importance; fruits are not much studied. Physical, physico-chemical, nutritional, inorganic ion and phytochemical analysis carried out in the present study showed the effect of maturation on chemical composition of this fruit. The % TTA of unripe and ripe fruits is very low (0.30 and 0.25 resp.) and 0Brix (4.0 and 9.0 reps.) indicate the bland taste of the fruits. Solid content in ripe fruit is 19%, crude fiber content is 4.36%; though the moisture content is higher, the nature of fruit is pulpy and not juicy because of high fiber content. The potassium content is significant in both unripe and ripe fruits. Succinic acid is found to be the predominant one followed by malaise, ranging from 104-113mg/100g and 100-104mg/100g respectively. Amongst total sugars fructose is prominent followed by glucose. Anthocyanin content in the peel of the ripe fruit is quite high and significant (2.10 g/100g). Both unripe and ripe fruits have a strong presence of phenolics and flavonoids. The cluster fig fruits have very good nutritional and mineral composition along with strong presence of phenolics and flavonoids. This shows its importance as a table fruit. It will be beneficial for human as it may have very good antioxidant activities as revealed by high phenolic content (0.78mg/g fresh wt. basis). Thus the present work shows that cluster fig fruit would be a potential source for food and pharmaceutical products.